Explant pathology in Biliary Atresia post Kasai procedure: a tale of two livers - Sunayana Misra; Sonia Badwal; Shashi Dhawan; Arpita Mittal; Naimish Mehta; Nishant Wadhwa; Arjun Maria (University of São Paulo, 2024)
Biliary atresia (BA) is a progressive inflammatory cholangiopathy of infancy that results in fibrous obliteration of the extrahepatic and intrahepatic bile ducts. In untreated patients, this leads to biliary-type cirrhosis within the first two years of life. Timely diagnosis of BA with a lack of significant hepatic fibrosis is critical and surgical drainage (Kasai procedure) within the first two months of life is the initial treatment modality with the highest success rate. Ultimately, liver transplantation is required due to surgical drainage complications, such as recurrent cholangitis, failure to thrive, and portal hypertension (PHTN). Histopathological findings of hepatectomy specimens after failed and successful Kasai procedures are vastly different depending on the subsequent course of liver disease. Bile flow is inadequate following a failed Kasai procedure with rapid development of biliary cirrhosis. Explants from patients with successful Kasai procedure may show cholestatic (recurrent cholangitis), vascular (obliterative venopathy, regenerative hyperplasia, and PHTN), or an interplay of both cholestatic and vascular abnormalities. Pathologists need to be aware of explant histopathology (post-successful Kasai procedures) with a clinical course dominated by PHTN for precise documentation of vascular abnormalities.